Education Transformation: Illocutionary in Nadiem Makarim’s Speech at the Education World Forum 2023 - Indah Jatiningtyas, Nurlaila; Hidayat, Didin Nuruddin; Alek, Alek; Susilo, Atiq (Universitas Cokroaminoto Palopo, 2024)
People communicate with each other with some intentions. Nowadays, information can be easily accessed through social media. Unfortunately, the platforms cannot understand the semantic and pragmatic features. To achieve effective communication, speech should be performed and interpreted accordingly. This article will discuss the illocutionary acts in Nadiem's speech. The speaker's purpose can be understood comprehensively by analysing the illocutionary acts. The present study is a descriptive-qualitative analysis. The main focus of this study is the illocutionary speech acts performance. The video gathered was about Nadiem Makarim, the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia, presenting the Education Transformation in Indonesia. The video was taken at the Education World Forum, London 2023. The researchers then transcribed the video, analysed the illocutionary speech acts, specified the types, and evaluated the corresponding frequently used speech acts percentages to derive the conclusions. It can be found that Nadiem Makarim has performed 107 utterances. The utterances used are categorised as assertive speech acts, which is prevalent up to 82 utterances. The other illocutionary speech acts presented are expressive, consisting of 14 utterances, ten directives utterances, and one commissive speech act. It can be concluded that the most frequently used illocutionary speech act in the speech is assertive, which takes accounts into 76.6%. There were not any declaratives illocutionary speech acts found